Graduates of a public university and perspectives of performance in Nursing management - Maria de Lourdes de Almeida; Aida Maris Peres; Elizabeth Bernardino; Marieta Fernandes Santos (Rev Rene)
A study with a qualitative approach aiming to analyze the influence of undergraduate education on preparing for management in Nursing. The study was conducted with 22 graduates from a Public University in Southern Brazil. This research had data collected between the months of February and April through semi-structured interviews. Data was analyzed by the Collective Subject Discourse technique. The study was approved by the Ethics Committee of the Federal University of Paraná. The following central ideas were found as a result: how undergraduate studies influence professional performance; use of managerial tools in managerial procedures; gaps found in subjects’ practical training sessions; suggestions for improvement. The research revealed fragmentation of subject contents, managerial procedures of doing with a productive approach, the need of curricular restructuring, improve training in the field and teaching/work partnership improvement. It is difficult for nurses to understand the managerial scope of its working process and to develop managerial competencies in professional practice.